Bentuk Code-mixing Bahasa Arab Santri dan Ustaz Pondok Pesantren Darussalam Parmeraan, Kabupaten Padang Lawas Utara: Pendekatan Sosiolinguistik - Ritonga, Arip Rachman; Rahmawati, Dini (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
The multilingual environment at Pondok Pesantren Darussalam Parmeraan, where santri and ustaz alternate among Arabic, Indonesian, and Batak Mandailing, creates a natural setting for code-mixing in daily communication. This study aims to identify the forms and directions of code-mixing, examine the motivations for its use, and analyze its sociolinguistic functions in both educational and social interactions. A descriptive qualitative approach was employed, with data collected through observation, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings indicate that the dominant forms of code-mixing are insertion, alternation, and congruent lexicalization, occurring outwardly (between Arabic and non-Arabic languages) and inwardly (between Indonesian and Batak Mandailing). Code-mixing functions as a communicative strategy, strengthens group solidarity, and reinforces religious identity within the pesantren community. This study contributes to understanding multilingual communication in Islamic educational settings and provides new insights into tri-lingual code-mixing, a rarely examined phenomenon in Indonesian sociolinguistics.